The heart and lungs of the petroglyph Sechin - Dejo Bustios, Hugo A. (2020)
In the Casma valley, 375 Km north of Lima, there lies Sechins archaeological site. There is an enormous stone wall surrounding the main building. There is where we found a petroglyph that we interpreted as a representation of the organs within the thoracic cavity.